Analisis Pendidikan Karakter Siswa Terhadap Pembelajaran Jarak Jauh (PJJ) - Wahyu Lutfi Ansori; Vernanda Ayu Pramesti; Fery Diantoro (Journal of Education and Religious Studies, 2021)
The purpose of this study was to determine the application of problem-based learning models (Problem Based Learning) to students' creative thinking abilities. Character Education is a must because education does not only make students smart. And in scientific research using library research (library research). Literature study is a type of research conducted with a researcher by collecting data from books, journals, articles and certain writings. In addition, it is also based on our observations about the development of online learning in Indonesia. The author uses descriptive-qualitative research methods. Qualitative research method is a research that is intended to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups. To overcome the problem of character education, it is necessary to have special attention from teachers and parents of students regarding how to talk, how to dress, student discipline, and how to get along with friends and the surrounding environment. "The problem of character education so far has existed in every education unit needs to be immediately studied. , and alternative solutions are sought, and they need to be developed in a more operational manner so that they can be implemented in schools easily. "The findings of this study are that there are three problems with character education of students, namely discipline problems, courtesy problems and student enthusiasm problems. The supporting factor of the cultivation of character education is the support of school activities. The inhibiting factor of this research is the lack of supervision in the cultivation of character education activities.